HERBAL MEDICINE PERCEPTION AND PRACTICE AMONG CHILDBEARING MOTHER WITH MEDICAL EDUCATION BACKGROUND IN BANDUNG: A PRELIMINARY STUDY - d’Arqom, Annette; Nasution, Zamal (Majalah Obat Tradisional, 2014)
Herbal medicine has been widely used among Indonesians as an alternative medicine to chemical based drugs. However, there is still a doubt about its effectiveness and efficiency. Many studies report that natural side of herbal medicine has healthier effect than additive or chemistry ingredient of chemical based drugs. Nowadays, there is a shifting in nurturing children among childbearing mother, including mother with medical education background, living in more nature. The aim of this study is to explore their perception and practice towards herbal medicine. Open-ended questionnaires were online distributed among 30 childbearing mothers with medical education background and analyzed using descriptive method. The result shows that 73% of respondents use herbal medicine such as honey (33.3%), onion (13.3%), lime (13.3%), etc. The less side-effect is a strongest point of their usages (45%), followed by mild illness treatment (36%), and natural ingredient (18%). Those respondents admitted the symptoms were reduced after using herbal medicine, but 81.6% of them would use chemical drugs when the symptoms persisted. Twenty seven percent of the respondents never used herbal medicine because of complicated preparation and unclear effect. However, the entire respondents said chemical drugs have a clear effect, and its effectiveness and efficiency even better than herbal medicine. Hence, it can be concluded that most respondents even though have medical knowledge would use herbal medicine on first medication for their children rather than chemical based drugs.Â